The impact of male genital self-image on depression, anxiety and sexual functions - Adil Emrah Sonbahar (The Aging Male)
Aim This study aims to examine the relationship between male genital self-perception and sexual functioning and depression anxieties.Method The study included male patients who were referred to the andrology outpatient clinic between March 2022 and June 2022. Demographic data of the patients were recorded. Cigarette and alcohol consumption was also noted. The Male Genital Self Image Scale (MGSIS) questionnaire was used for the Genital Self Image(GSI) assessment, which consists of 7 questions. The International Index of Erectile Function (IIEF), composed of 15 questions, was used to evaluate sexual function. STAI-I, STAI-II, and BECK scales were used for depression and anxiety. The penis size of the patients was measured in a flask and stretched condition, and the midpenile circumference was recorded. Patients were compared with respect to GSI, depression, anxiety, and sexual functioning.Results A total of 75 patients were included in the study. The mean age of the patients was 46.69 ± 11.32 (26–72), and the mean BMI was 27.82 ± 3.79 (22.46–40.40) kg/m2. A slightly positive correlation was found between the patients’ flask penis size and MGSIS-total scores (r = 0.260, p = .024) and IIEF-SF scores (r = 0.240, p = .038). There was a moderately positive correlation between the stretched penis size and IIEF-OS (r = 0.403, p < .001) and IIEF-SF (r = 0.354, p = .002). While the MGSIS-total score and the STAI-I and STAI-II scores had a moderate negative correlation, there was an advanced negative correlation between the MGSIS-total score and the BECK score.Conclusion Disruption of men’s genital self-perception is moderately related to their susceptibility to depression and anxiety. This situation affects the person’s sexual performance and causes orgasm problems to increase.